2020
DOI: 10.1111/ctr.14115
|View full text |Cite
|
Sign up to set email alerts
|

The impact of donor and recipient diabetes on renal transplant outcomes

Abstract: The use of diabetic kidneys is increasing worldwide with better outcome than being on waitlist and possible reversal of diabetic changes in transplanted kidneys. But particular caution is warranted in diabetic donor-recipient combination. Total 1223 deceased donor kidney transplants were performed at our center between 2008 and 2018. 689 from non-diabetic donor (NDD) to non-diabetic recipient, 400 from nondiabetic donor to diabetic recipient, 97 from diabetic to non-diabetic recipient, and 32 from diabetic don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 23 publications
(35 reference statements)
1
5
0
Order By: Relevance
“…Limiting time on dialysis is beneficial and a pretransplant dialysis duration >24 months has been found to be a significant risk factor associated with poor death-censored graft survival [ 40 ]. Regardless of the origin of the donor organ, adjusted mortality rates are 75% higher with rates of adjusted graft losses 25% higher in diabetic recipients [ 41 , 42 ]. This may be more likely related to the highest 2-year mortality in this cluster.…”
Section: Discussionmentioning
confidence: 99%
“…Limiting time on dialysis is beneficial and a pretransplant dialysis duration >24 months has been found to be a significant risk factor associated with poor death-censored graft survival [ 40 ]. Regardless of the origin of the donor organ, adjusted mortality rates are 75% higher with rates of adjusted graft losses 25% higher in diabetic recipients [ 41 , 42 ]. This may be more likely related to the highest 2-year mortality in this cluster.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic donors’ potential to expand the donor pool has been extensively analyzed in large cohort studies; it has been ascertained that receiving a kidney from a DD does assure a survival benefit, compared to remaining on the waiting list and that patient and graft survival depend on the status of the recipient. Indeed, the worst outcomes are seen when diabetes is present in both the donor and the recipient, and the diabetic recipient of a non-diabetic kidney has a worse evolution then a non-diabetic recipient [ 3 , 4 , 10 , 12 , 13 ]. Although the differences in organ and patient survival rates between diabetic and non-diabetic donors are slight, the discard rate of DD is still too high and these organs are not utilized at their fullest potential [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The donors in our cohort had the highest number of years (54–77 y–o) and KDPI (80–100%) compared to the other published records. Singh et al have recently reported 10-year graft and patient survival data analyzing the mis- matches in donor and recipient diabetes status; they reported a mean donor age of 36–51 years in the different groups, while the donors in the group DD- ND recipient had a mean age of 47 and a mean KPDI of 71% [ 4 ]. Similarly, Kahn describes a population of 38-year-old donors, 45-year old in the match DD-ND recipient [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations